Empowering New Capital Zones: East Kalimantan’s Economic District Outlooks Using Location Quotient and Cluster Analysis - Mega Silfiani; Diana Nurlaily; Irma Fitria ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2024)
This research focuses on investigating the economy of the new capital buffer zone by identifying and clustering its leading sectors in GRDP (Gross Regional Domestic Product) of East Kalimantan. The identification of a region’s leading sector through LQ (Location Quotient) index has proven to be effective. In addition, k-means clustering and Self-Organizing Maps (SOM) are adopted to provide comprehensive insights. The results show that LQ index quickly identifies the main sectors in each district of East Kalimantan. In addition, the kmeans clustering has better performance than SOM based on the Silhouette coefficient. This meticulous analysis confirms the existence of two distinct clusters, one including eight members and the other consisting of only two. Anticipating future research endeavours, the exploration of various approaches for constructing clusters, encompassing both hierarchical and non-hierarchical approaches, provides the potential to enhance the performance of clusters. By investigating this structure, a more comprehensive comprehension of the economic framework of East Kalimantan can be achieved, as well as its potential role as a buffer for the capital region.